Human-black bear conflict: crop raiding by Asiatic black bear (Ursus thibetanus) in Azad Jammu and Kashmir, Pakistan - Ali,U. (2024)
Abstract Asiatic black bear has long been in conflict with human beings crop raiding is a major cause of this conflict frequently noted in South Asia. Crops raided by black bears affected by temporal, spatial and anthropogenic attributes. Insight in this conflict and its mitigation is vital for the conservation of this threatened species. Present study aimed to evaluate crop raiding by black bears in the mountainous region of Azad Jammu and Kashmir. Field surveys were carried out to observe spatial and temporal crop raiding features between 2015-2020 and data gathered using designed questionnaires randomly tailored in villages nearby the forests. Results revealed that maize was the sole crop raided by black bears. A total of 28-acre area was raided by black bear in the fall season (Aug-November) resulting in a damage of 51 metric tons, whole raiding was carried out at night. Each respondent received crop damage on 0.09 acre with a loss of 0.17 metric ton yield. Crop quantity and area were significantly correlated to each other. District Neelum shared 49% of the total crop loss, while 47% of the maize was raided at the altitudinal range of 2100-2500 m. crop raiding was highly significantly ( χ 2 = 1174.64 ; d f = 308 ; p < 0.01) dependent upon distance to the forest. Linear regression revealed that maize quantity was determined by area, time and the total field area. Farmers faced 3.8 million PKRs loss due to crop damage by black bears. Despite the huge loss, the majority (23%) of the respondents did not respond to the query on mitigation measures indicating a poor adaptation of preventive measures. Preferred strategy to avoid crop damage was making noise (27.8%) when bears attacked their crops. A start of compensation scheme to the farmers is recommended that will have turned their negative attitude into a positive one toward the wildlife and black bear particularly. Study provides a new insight in human-bear conflict, particularly in spatial and temporal context of crop raiding in AJ&K.